CHALLENGES AND CONTROVERSIES IN OBSTETRICS: A REVIEW OF CURRENT EVIDENCE ON OBSTETRIC COMPLICATIONS AND THE USE OF OCYTOCIN IN LABOR AND DELIVERY - Saraiva Sales, Jandir; Vinicius da Silva Pereira, Marcus; Vinícius Soares Silva, Marcos; Carolina Gonçalves Pires, Ana; Douglas Lopes Leite, Jadson; Duarte Silva, Letícia; Nayara Coelho Muniz Cardoso, Monique; Soares da Costa, Douglas; Saraiva Sales, Eider; Mikaelly Santos da Silva, Mara; Victor Costa Lacerda de Sousa, João; Vinicius Magalhães Guedes, Marcus (Health and Society, 2023)
This article provides a comprehensive review of current evidence on the challenges and controversies in obstetrics, with a focus on shoulder dystocia, fetal monitoring, and the use of oxytocin in labor and delivery. A systematic search was conducted in three databases (Scielo, Google Scholar, and LILACS), resulting in the selection of 10 relevant studies for an integrative review. The studies encompassed various research methodologies, including systematic reviews, cohort studies, clinical trials, qualitative studies, and narrative reviews. The findings provided important insights into the investigated topics, including risk factors associated with shoulder dystocia, effectiveness of fetal monitoring, comparison of oxytocin use protocols, women’s experiences with shoulder dystocia, obstetric complications, controversies surrounding oxytocin use, incidence of shoulder dystocia, and utilization of fetal monitoring. These findings contribute to a better understanding of these topics and may guide clinical practice towards safer and more effective obstetric care. However, further research is needed to fill existing knowledge gaps and inform evidence-based decision-making in obstetrics.